User perception of endocervical sampling: A randomized comparison of endocervical evaluation with the curette vs cytobrush. - Manuela Undurraga; Rosa Catarino; Isabelle Navarria; Yasmine Ibrahim; Evelyne Puget; Isabelle Royannez Drevard; Jean-Claude Pache; Jean-Christophe Tille; Patrick Petignat (PLoS ONE, 2017)
To evaluate whether the endocervical brush (ECB) is better accepted by patients and health care providers for endocervical evaluation when compared to the endocervical curette (ECC), without a decrease in the quality of sampling.Two hundred patients with cervical dysplasia were randomized at the colposcopy clinic of the University Hospital of Geneva into two groups according to technique. Patients and physicians' preference regarding the technique as well as the quality of samples were assessed. ECB samples were analyzed using both cytological (cell block) and histologic analysis, while ECC samples were analyzed using standard histologic analysis.Of the 200 patients, 89 were randomized to ECC, 101 to ECB and 10 were excluded due to incomplete information or cervical stenosis. Physicians preferred ECB against ECC, classifying it more frequently as an easy technique (94.1% vs.61.4%, p<0.001). Physicians more frequently evaluated the ECB as little or not uncomfortable for patients (28.7% vs.10.2%, p<0.001), though patients themselves didn't express a preference for either technique. From a quality standpoint, the brush allowed for a better quality of samples, with a lower rate of inadequate samples (2.0% vs 14.3%, p = 0.002) and greater amount of material.Endocervical sampling using ECB seems to be easier to perform and provides better quality samples. ECB can therefore be an acceptable alternative to ECC in standard practice.ClinicalTrials.gov NCT01435590.